Some aspects of the reproductive biology and sex-ratio of Cirrhina reba (Hamilton) (Cyprinidae : Cypriniformes) (University Journal of Zoology, Rajshahi University, 2012)
Some aspects of the reproductive biology viz. sex-ratio gonadal length index (G.L.I.), gonado somatic index (G.S.I.) and sex-ratio of Cirrhina reba were studied during September 2004 to July 2005. In present study the highest values of GLI (33.76) and GSI (0.63) were in the month of July. Total length (TL) and gonadal length (GL), total weight (TW) and gonadal weight ( GW ), standard length (SL) and gonadal length ( GL ) and gonadal weight relationships were found to be positive; and the relationships were: GL = -3.873 + 0.219 TL (r = 0.992), GW = 0.01511+0.000815 TL (r = 0.979), GL = -2.6030+0.253 SL (r = 0.990), GL = 0.01997+0.000938 SL (r= 0.976), GW = 13.2952+0.6064 TW (r = 0.958), GW = 0.0772+0.00233 TW (r = 0.979). The sex- ratio of C. reba were 1:1.62 for male and female respectively. The Chi-square test showed significant differences of sex-ratio among months and totals.DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10739Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 21-24